Rotational vs. laser atherectomy in Chinese CTO-PCI: lesion-specific efficacy with comparable midterm safety - Chen, Liansheng; Huang, Zehan; Wu, Quanmin; Deng, Huiliang; Huang, Meiping; Xu, Yiqi; Wei, Jinkun; Liu, Yong; Xie, Nianjin; Huang, Yuming (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic total occlusion (CTO) percutaneous coronary intervention (PCI) often requires plaque modification for device delivery. While rotational atherectomy (RA) and excimer laser coronary atherectomy (ELCA) are established adjuncts, their comparative efficacy and safety remain underexplored in Chinese populations.MethodsThis single-center retrospective study included 75 consecutive CTO-PCI patients treated with ELCA (n = 25) or RA (n = 50). Procedural success, complications, and major adverse cardiovascular and cerebrovascular events (MACCE) were analyzed over a median 17.5-month follow-up. Multivariable Cox regression adjusted for calcification severity, lesion length, ISR-CTO, and diabetes mellitus.ResultsRA was preferred for moderate/severe calcification (76% vs. 48%, p = 0.020), while ELCA dominated in ISR-CTO (20% vs. 2%, p = 0.024) and lesions >20 mm (56% vs. 30%, p = 0.044). Procedural success was comparable (RA 90% vs. ELCA 84%, p = 0.706). Procedure-related complications differed: RA had two coronary perforations (4% vs. 0%, p = 0.130), whereas ELCA showed a trend toward more transient slow/no-reflow (12% vs. 0%, p = 0.061). MACCE rates remained similar (19% vs. 13.3%, p = 0.815; adjusted HR 1.53, 95% CI 0.35–6.65, p = 0.569). Both techniques exhibited comparable procedural duration and radiation exposure (all p > 0.05). ELCA incurred higher total costs (US11,147 vs. 9,267, p = 0.007), driven by laser catheter expenses; however, procedural costs became comparable after excluding catheter-related expenditures (p = 0.210).ConclusionIn Chinese CTO-PCI, ELCA and RA demonstrate lesion-specific utility—ELCA for ISR-CTO and long lesions, RA for calcified lesions—with comparable midterm safety. Procedural costs of ELCA and RA were equivalent in Device-excluded costs analysis.